THE USE OF THE NOC CLASSIFICATORY SYSTEM IN CONDITIONS OF INTENSIVE CARE - Hůsková, Jitka; Juřeníková, Petra (Profese Online, 2013)
Aim: The evaluation using of cardiopulmonary class NOC outcomes of classificatory system in the relation to 00031 NANDA-I. Ineffective Airways Clearence diagnosis. With a view to testing use classificatory systems NNN by nurses in the real clinical workplaces of intensive care.Methods: Nurses evaluated using the outcomes array of NOC cardiopulmonary class of the classificatory system (4th edition, 2008) which they would really use in their clinical workplaces in the relation to fixed nursing diagnosis 00031 NANDA Int.-Ineffective Airways Clearence (NANDA-I, 2009-2011, translation Kudlová, p. 360). They evaluted with help of Likert type scale into recording list. For NOC outcome evalution comparison by nurses from individual clinical workplaces Pearsen chi-square test for independency was used after the basic statistical processing (arithmetic mean, median, standard tolerance.Results: Research did not prove statistically significant differences of nurses (n65)evalution at outcomes 0412; 0415; 0416; of NOC cardiopulmonary class of the classificatory system.Conclusion: The research enquiry brought partial results to IGA MZČR NF 12078-4/2011 project which supports implementation of NIC classificatory system in surgical and anaesthetic nursing care into the conditions of clinical practice of the Czech Republic.
Keywords: NNN Classification; Ineffective Airway Clearence; Intensive Care; Airways